Предмет: Алгебра,
автор: aisuludusheeva
Упростите выражение 1) (x-2y^2)^2 - ( x+2y^2) ^2
2) (4x^2+y^2) (2x+y) (2x -y)
Ответы
Автор ответа:
0
1)x²-4xy²+4y⁴-(x²+4xy²+4y⁴)=x²-4xy²+4y⁴-x²-4xy²-4y⁴=-8xy²
2)4x²+y²(4x²-2xy+2xy-y²)=4x²+4x²y²-2xy³+2xy³-y⁴=4x²+4x²y²-y⁴
2)4x²+y²(4x²-2xy+2xy-y²)=4x²+4x²y²-2xy³+2xy³-y⁴=4x²+4x²y²-y⁴
Похожие вопросы
Предмет: Химия,
автор: LediTA
Предмет: Физика,
автор: aanaisenalieva4
Предмет: Биология,
автор: lunamx
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: bbakytgul